Energy Performance of an All Solid State Electrochromic Prototype for Smart Window Applications. (November 2015) - Piccolo, A.; Simone, F.
Abstract: Electrochromic devices suitable for architectural applications must exhibit acceptable levels in specific performance indicators to carry out useful energy saving functions. These parameters indicate the global response of the window to the solar radiation and completely determine the energetic performance of the glazing. In this paper we present performance data of a home-made all solid state prototype which meets most of the basic requirements. The device is characterized by a visible transmittance modulation between around 68 and 14% (in the full bleaching and colouring states respectively) and demonstrates repeatable behavior after 12h cyclization.